2018
DOI: 10.32014/2018.2518-170x.36
|View full text |Cite
|
Sign up to set email alerts
|

Computer Modeling of Creep for Hereditary Materials by Abel’s Kernel

Abstract: NAS RK is pleased to announce that News of NAS RK. Series of geology and technical sciences scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Science offers to researchers, authors, publishers, and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The improved methods for determination of the parameters λ, α, β have been developed in the works [49,50], and it is shown that the unsteady-state creep for an asphalt concrete can be approximated with a high accuracy using the Rabotnov'slinebreak fractionexponential function.…”
Section: Creep Kernelmentioning
confidence: 99%
See 2 more Smart Citations
“…The improved methods for determination of the parameters λ, α, β have been developed in the works [49,50], and it is shown that the unsteady-state creep for an asphalt concrete can be approximated with a high accuracy using the Rabotnov'slinebreak fractionexponential function.…”
Section: Creep Kernelmentioning
confidence: 99%
“…The works [38,50] show the possibility for description of the unsteady-state creep of an asphalt concrete with a high accuracy by more simple expression than Equation (3).…”
Section: Creep Kernelmentioning
confidence: 99%
See 1 more Smart Citation
“…The works [5][6][7][8] suggest the parameter to consider as the specified one, and the remaining two other parameters to determine using the least squares method. In the work [9] the above method has been improved: the determining ratios have been changed by introducing the so-called experimental rheological parameter.…”
Section: Relaxation Kernel Parametersmentioning
confidence: 99%
“…Creep and relaxation are important characteristics of hereditary materials. The creep has been studied for an asphalt concrete and other materials in the works [5][6][7][8][9][10][11][12][13]. The present work is devoted to the modeling of the process for relaxation of a number of hereditary materials.…”
Section: Introductionmentioning
confidence: 99%